Females of southeastern United States species of Brachycentrus Curtis, 1984 (Trichoptera: Brachycentridae). Issue 3 (3rd July 2019) - Wrege, Coleson F.; Morse, John C.
Abstract: From 10 species of Brachycentrus Curtis, 1834 known from the southeastern United States, female genitalia of only five have been described so far. Herein, for the first time, we describe female genitalia of the following Brachycentrus species: B. appalachia Flint, 1984, B. chelatus Ross, 1947, B. lunatus Harrington and Morse, 2004, B. solomoni Flint, 1984 and B. spinae Ross, 1948 . Female genitalia of B. etowahensis Wallace, 1971 are re-described. These were prepared from specimens of the Clemson University Arthropod Collection, Illinois Natural History Survey, US National Museum of Natural History, and from specimens collected in two streams in North Carolina. Based on characters of the female genitalia, a dichotomous key to all 10 southeastern US Brachycentrus species is included. Diagnostic characters are noted in the ventral and lateral shapes of fused abdominal segments IX/X, lobes of abdominal sternite VIII, and spermathecal sclerite.